The Influence of Farm Road Construction on Agriculture in Banjarnegara Regency - Diah Setyorini Gunawan; Icuk Rangga Bawono; Rifda Naufalin; Hery Awan Susanto; Anzar Alfat Firdaus (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Farm roads are essential infrastructure that support agricultural business activities by improving access and transportation efficiency. This research aims to assess the impact of farm roads on agricultural productivity and to explore the related challenges and opportunities in Banjarnegara Regency. The study employs both primary and secondary data, with primary data collected through survey methods. Respondents were rice farmers from eight sub-districts in Banjarnegara Regency, providing diverse insights into local farming conditions. The data were analyzed using the Wilcoxon test. The findings reveal a significant difference in farmer productivity prior to and following the construction of Farm Roads. The majority of respondents (60.34 percent) experienced an increase in productivity, indicating the presence of farm roads in Banjarnegara Regency has a beneficial effect on the local agricultural community. However, 13.79 percent of respondents reported a decline in productivity, while 25.87 percent had no change in productivity. The challenges and potential related to Farm Roads in the surveyed areas are largely representative of those in other areas of Banjarnegara Regency. This issue warrants attention from relevant local government agencies, as adequate Farm Roads are essential for farmers. These roads are not only vital for accessing farmland but also for transporting agricultural inputs and harvests. Improved access and transportation can significantly enhance agricultural productivity in Banjarnegara Regency.